The impact of having natural teeth on the QoL of frail dentulous older people. A qualitative study - Niesten, Dominique (BioMed Central, 2012)
BACKGROUND: In order to adapt oral care and treatment to the demands of the growing group of frail dentulous older people, it is important to understand how and to which extent having natural teeth contributes to the quality of life (QoL) of frail older people and how frailty influences their perspective. METHODS: A qualitative approach was used. Interviews with 38 Dutch frail older dentulous people were tape-recorded, transcribed, coded for content and analyzed. Additional information was collected which included age, gender, living situation, use of dental prostheses, self-reported oral health status, chronic disorders, and an index for frailty. RESULTS: Seven themes were identified in the relationship between natural teeth and the QoL of the participants: pride and achievement; intactness; sense of control; oral function; appearance; comfort; along with coping and adapting to disabilities. Having natural teeth generally had a positive effect on QoL. Positive effects through pride and achievement, intactness, and sense of control were most apparent for the most severely frail. They compared themselves with peers who are more often edentate, and valued the good state of their teeth against the background of their declining health, especially those with disabilities causing severe chronic pain or impaired fine-motor skills. The effect of coping with and adaptation to tooth loss was also most apparent for the most severely frail. There was a gender effect in that the men generally cared less about having natural teeth than women, regardless of their level of frailty. CONCLUSIONS: QoL of frail older people is positively influenced by natural teeth, and this effect seems to increase with increasing frailty. Preservation of teeth contributes to a positive body image and self-worth. Oral care for frail people should aim to preserve natural teeth if possible.